Introduction to probability models : operations research . - Winston, Wayne L. (Brooks/Cole-Thomson Learning, 2004)
CD-ROM contains student editions of: ProcessModel, LINGO, Premium Solver, DecisionTools Suite including @RISK AND RISKOptimizer and data files